Basic statistics for business and economics - Lind, Douglas A.; Marchal, William G.; Wathen, Samuel Adam (McGraw-Hill/Irwin, 2013)
Suitable for students majoring in various fields of business administration, this title provides an introductory survey of the many applications of descriptive and inferential statistics